The effects of docosahexaenoic acid supplementation on cognition and well-being in mild cognitive impairment: A 12-month randomised controlled trial - Mengelberg A; Leathem J; Podd J; Hill S; Conlon C (John Wiley and Sons, Ltd, 2022)
OBJECTIVES: Several recent clinical trials have shown that docosahexaenoic acid (DHA) supplements have a significant effect on cognition in cognitively impaired older adults. This randomised controlled trial aimed to investigate the cognitive effects of a DHA fish oil supplement in older adults with mild cognitive impairment, and to examine the moderating effect of the apolipoprotein E (APOE) ɛ4 allele on cognition and well-being. METHODS/DESIGN: Seventy-two older adults between the ages of 60 and 90 from New Zealand were given a DHA supplement equivalent to 1491 mg DHA + 351 mg eicosapentaenoic acid per day or a placebo for a period of 12 months. Outcome measures included cognition, wellbeing and self-rated quality of life as well as height, weight, blood pressure and APOE genotyping. RESULTS: The final analysis (n = 60) found no evidence of a treatment effect on cognitive measures, although did find a treatment effect on systolic blood pressure (p = 0.03, ƞ2  = 0.08), and a treatment interaction for APOE ɛ4 carriers on depression (p = 0.04, ƞ2  = 0.07) and anxiety (p = 0.02, ƞ2  = 0.09) scores in favour of the DHA supplement. CONCLUSIONS: Despite no effect on cognition, the positive result in APOE ɛ4 carriers on depression and anxiety scores and on systolic blood pressure justifies further DHA trials. It may be a prudent step going forward for more studies to replicate the design elements (dose, duration and cognitive measures) of previous DHA trials to help understand why not all older adults appear to benefit from taking a fish oil supplement.
(c) 2022 The Author/s
Keywords: APOE ɛ4 carriers; DHA; EPA; mild cognitive impairment; Aged; Cognition; Cognitive Dysfunction; Dietary Supplements; Docosahexaenoic Acids; Double-Blind Method; Humans; Quality of Life